Teknik Relaksasi Genggam Jari Terhadap Tingkat Kecemasan Pasien Preoperatif Apendicitis Di RSUD Sekarwangi - Yeni Yulianti; Annisa Nur Hidayah (HealthCare Nursing Journal, 2023)
Anxiety in pre-surgery can cause surgery to be delayed, can prolong the recovery process, reduce immunity to infection, increase the use of analgesics, and lengthen the time of stay. This study aims to determine the effect of the finger technique on the level of anxiety in preoperative appendicitis patients at Sekarwangi Hospital, Sukabumi. Finger grip relaxation can control and restore emotions that will make the body relax. When the body is relaxed, muscle tension is reduced and anxiety is reduced. This research was conducted in the Nyi Ageng Serang room at Sekarwangi Hospital, Sukabumi from 14 May to 13 June 2018. The study used a pre-experimental research design type One group pre-post-test design with a total sample of 18 people with accidental sampling. Based on the median research value of anxiety before the intervention was 47.9 while after the intervention was 42.5.